Relevansi Prinsip-prinsip Hukum Ekonomi Syariah dalam Membangun Keadilan Sosial melalui Distribusi Ekonomi yang Adil - Sulistiyo, Budi; Rasyid, Fauzan Ali; Saleh, Chaerul (AHKAM, 2024)
This study aims to investigate the relevance of the principles of Islamic economic law in shaping social justice through equitable economic distribution. In the midst of global economic change, reducing economic inequality and social injustice is very important. Islamic economic law, as a framework rooted in Islamic values, offers a unique view of economic distribution that focuses on the principle of justice. By conducting an in-depth literature review and analysis, this study explores the concept of Islamic economic law, the principles contained in it, and its relevance to the goal of achieving social justice. We identify the important role of zakat, infaq, and waqf in creating equitable distribution and fueling inclusive economic growth. The results of this study show that the principles of Islamic economic law have great potential to influence economic and social policies in Islamic societies, ultimately encouraging the creation of a more just and inclusive economic environment. However, we also identified some obstacles to the implementation of these principles. This research makes an important contribution to our understanding of how the principles of Islamic economic law can be applied in the current context to promote social justice as well as more equitable economic distribution. The policy recommendations that emerge from the results of this study can guide decision-makers in their efforts to achieve social justice in Islamic societies.